Vo2max Level of Unsika Swimming Athletes - Ruslan Abdul Gani; M.E. Winarno; Irfan Zinat Achmad; Rhama Nurwansyah Sumarsono (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2020)
VO2max is an important component to improve an athlete’s performance. VO2max is an absolute aspect for athletes to improve their performance. By having a high level of physical fitness, targets in exercise will be achieved optimally. This study was aimed at determining the level of maximum ability (VO2max) of UNSIKA swimming athletes. It applied a survey method with a quantitative descriptive approach. The population of the study were 20 students from UNSIKA swimming club. The sampling was performed by using saturated sampling (total sampling) where all members of the population become members of the sampling, thus the samples were 20 swimming athletes. The data were collected through a swimming test for 12 minutes with the standardized norm from the 12-minute Cooper swimming test. The results illustrated that the swimming athletes with 'very good' VO2max level category were 3 athletes (15%), the 'good' VO2max level category were 4 athletes (20%), the 'fair' VO2max level category were 3 athletes (15%), the 'poor' VO2max level category were 4 athletes (20%), and the 'very poor' VO2max level category were 6 athletes (30%). The study concludes that the VO2max level of UNSIKA swimming athletes was in the 'very poor' category.AbstrakVO2Max ialah komponen penting dalam meningkatkan prestasi atlet, VO2max merupakan aspek mutlak bagi atlet untuk meningkatkan penampilan dalam prestasinya, dengan memiliki tingkat VO2Max yang tinggi maka targetan dalam latihan akan tercapai dengan optimal. Penelitian ini bertujuan mengetahui tingkat kemampuan maksimal (VO2Max) atlet renang Unsika, metode yang digunakan dalam penelitian ini dengan metode survey dengan pendekatan kuantitatif deskriptif, populasi dalam penelitian ini mahasiswa Klub Renang UNSIKA dengan jumlah 20 orang. Tehnik pengambilan sampling menggunakan sampling jenuh (total sampling) dimana semua anggota populasi menjadi anggota sampling dengan jumlah 20 atlet. Instrument pengambilan data dengan tes renang 12 menit,dengan norma yang telah baku dari Cooper swimming test 12 minute. Hasil penelitian menggambarkan tingkat VO2Max atlet renang dengan kategori baik sekali 3 atlet (15%) kategori baik 4 atlet (20%) kategori cukup 3 atlet (15%) kategori Kurang 4 atlet (20%) kategori kurang sekali 6 atlet (30%). kesimpulan dari penelitian ini bahwa tingkat kemampuan vo2max atlet renang unsika pada kategori kurang sekali